Meningkatkan Kemampuan Bahasa Inggris Peserta didik melalui Program ‘Engfluence’: Kursus Interaktif - Jabu, Baso; Nur Aeni; Fauzan Hari Sudding; Chaerul Fadlan Saud; Asriati; Amsar Ramadhan; Ani Putri Aneliya; Arjuna Al Albani Ilyas; Dhin Rizky R. Junaid; Nur Alya Triana (Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
The Engfluence program is an interactive E-Learning-based course designed to improve students' English skills at SMAN 2 Makassar. This program was implemented in response to students' low English proficiency, particularly at the Elementary level (A1-A2 CEFR), as identified through pre-tests and classroom observations. The action research method was employed, involving problem identification, data collection, planning, implementation, and evaluation. The program utilized digital platforms such as Google Meet, Canva, Wordwall, Kahoot, and Quizizz to create interactive and engaging learning experiences. Evaluation results indicated significant improvements in students' English proficiency. The Beginner class (A1-A2) showed an average score increase of 23 points (from 52 to 75), while the Intermediate class (B1-B2) improved by 17 points (from 65 to 82). Key success factors included an intensive and structured learning approach, level-based class division, and the use of interactive digital media. The program not only enhanced students' understanding of the material but also boosted their confidence in using English for communication.